Legal Protection for Children Victims of Narcotics Abuse in Riau Province - Daeng, M. Yusuf; Daeng Yusuf, Muhammad Fadly (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2021)
Narcotics abuse can be categorized as a criminal act as regulated in Law Number 35 of 2009 concerning Narcotics. The method used in this research is socio-legal research. In Law Number 35 of 2009 concerning Narcotics, there is no distinction between the abuse committed by children who are already drug addicts and children who are victims of narcotics abuse and are taking narcotics for the first time, so that these children are combined at the time of the crime. It is hoped that there will be political will from the Government of the Republic of Indonesia to revise Law Number 35 of 2009 concerning Narcotics in order to provide legal protection for children who are victims of narcotics abuse. One of the obstacles faced by the Riau Regional Police in eradicating narcotics abuse by children is the minimal role of parents who are willing to report their children. Therefore, the Riau Regional Police should cooperate with religious leaders from MUI, traditional leaders from LAM Riau, as well as community leaders in order to provide enlightenment to the public about the dangers of narcotics abuse for the future of children.